Entre Avignon et Paris : la double agence Franque au XVIIIe siècle - Béatrice Gaillard (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The purpose of this study is to present the office, organization and strategy of the Franque architectural agencies in Avignon and Paris. While the funds of the agencies have been scattered and lost, the analysis is based on the reading of private sources, notably a correspondence and a journal that take us into the intimacy and daily life of these architects. These documents also allow us to understand how these architects surrounded themselves in order to respond to the many commissions they received. Their collaborators were numerous, notably within their offices for the purpose of creating plans, drawings and contracts, but also on the building sites, whose management was supervised by trusted associates.